THE AIRCRAFT ACCIDENT RATE IN CIVIL AVIATION DURING AIR TRANSPORT OPERATIONS AT THE AIRPORT - Запорожець, О.; Государська, І. (Proceedings of National Aviation University (archive), 2012)
The aircraft accident dates in civil aviation Ukraine and in republics of participants Agreement werecollected. The aircraft accident rate per 1 million flights was defined for civil aviation Ukraine and republicsof participants Agreement. Dynamics of aircraft accident rate was represented for civil aviation Ukraine.This dynamics was done for civil aviation of republics of participants Agreement and worldwide.